Pengembangan Model Self Regulation Berbasis Protection Motivation Theory Terhadap Manajemen Perawatan Diri Pada Pasien Gagal Jantung: A Literature Review - Pratama, Shafaat; Sriyono, Sriyono; Wahyudi, Andri Setiya (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Factors affecting recurrent hospitalization in patients with heart failure are non-compliance with medication, fluids, and diet. Compliance with medication, dietary and fluid restriction, and weight of the body are part of self-care management. The study aims to improve self-care management in heart failure patients. Literature reviews are used to identify articles through Scopus, ProQuest, PubMed, and CINAHL databases. The inclusion criteria are open access, in English, with full-text articles published between 2016 and 2022 with the keywords "self-regulation", "protection motivation theory" and "heart failure". A total of fifteen articles were reviewed to answer research questions. The data is analyzed by the PRISMA chart. The results of the literary study showed that there were 15 articles that met the inclusion criteria. There are eight studies that use randomized controlled trial designs; seven titles use cross-sectional designs; and one study uses qualitative designs. Results show that better self-care can improve outcomes, reduce the incidence of recurring hospitalizations, and reduce the burden of treatment for heart failure patients. Self-efficacy can also be predicted from self-care behavior. It can be concluded that self-regulation is significantly linked to self-management behavior, and self-adjustment programs are known to be effective in improving self-care behaviors in heart failure patients.